PSYCHOLOGICAL READINESS & JOB READINESS TRAINING: UPAYA MEMBANGUN KESIAPAN SARJANA BARU UNTUK BEKERJA DI ERA MASYARAKAT EKONOMI ASEAN - Marina Sulastiana; Rezki Ashriyana Sulistiobudi (Jurnal Ilmiah Psikologi Terapan, 2017)
Unemployment in Indonesia, especially in human resource competition of MEA era is not only occurring on low educated workforce, but also on higher educated (Bachelor). Whereas, “obtain jobs not more than 4 months after graduating” is one of the performance indicator in University,  Fresh Graduate should be the determinant of Organization’s/Company’s sustainability and development. They should have readiness to face the high work demands. Readiness at work,  consists of ability (job readiness) and willingness (psychological readiness). The need analysis on Fresh Graduates of PTN-X Bandung shows that most of them need proper training to increase their readiness in entering working world. Therefore, it is important to do readiness training which called “Psychological Readiness and Job Readiness Training” for Fresh Graduate of PTN- X in Bandung. This research is an action research with one group pretest–posttest design experimental approach. The result of this research shows that “Psychological Readiness & Job Readiness Training” program is effective and plays a role in  increasing Fresh Graduates’ readiness at work. The Increasing is more on  Willingness/Psychological Readiness aspect than Ability/Job Readiness aspect,  quite significantly in knowledge and the level of  readiness at work.Key words: Readiness at work, Willingness (Psychological Readiness), Ability (Job Readiness), Fresh Graduate  Pengangguran di Indonesia khususnya dalam persaingan tenaga kerja di era MEA tidak hanya terjadi pada angkatan kerja  berpendidikan formal yang rendah, namun juga pada sarjana.Padahal “mendapat pekerjaan tidak lebih dari 4 bulan sejak kelulusan” merupakan salah satu indikator kinerja Prodi Sarjana di Perguruan Tinggi. Sarjana baru seyogyanya termasuk Sumber Daya Manusia penentu keberlangsungan dan kemajuan organisasi/perusahaan. Mereka selayaknya memiliki  kesiapan ( Readiness) dalam bekerja,  untuk dapat menghadapi tuntutan kerja yang tinggi. Kesiapan dalam bekerja terdiri dari kemampuan/ Kesiapan tugas (ability/Job Readiness)  dan  kemauan/ Kesiapan Psikologis (willingness/Psychological Readiness). Analisis kebutuhan pada sarjana baru di PTN-X Bandung, memperlihatkan bahwa sebagian besar dari mereka  membutuhkan pelatihan yang dapat meningkatkan Kesiapan di pekerjaan. Oleh karena itulah penting mengadakan pelatihan Kesiapan dalam bekerja yang disebut  Psychological Readiness  and Job Readiness Training bagi sarjana baru di PTN-X. Kajian ini bersifat action research  dengan pendekatan eksperimental  one group pretest-posttest design.  Hasil kajian menunjukkan program Psychologocal Readiness & Job readiness Training efektif,  berperan terhadap peningkatan Kesiapan dalam bekerja sarjana baru, lebih menonjol pada aspek Kemauan/Psychological Readiness daripada aspek Kemampuan/Job Readiness, cukup signifikan peningkatan di segi pengetahuan maupun taraf kesiapan dalam bekerja.Kata kunci: Kesiapan dalam bekerja, kemauan (Kesiapan Psikologis), kemampuan (Kesiapan Tugas),   Sarjana baru.